The perinatal loss and parental reflection - Kamile Kukulu (Dicle Medical Journal, 2010)
In this review, the causes of prenatal losses, pregnancy termination and reflection of this situation for the parents were investigated. Despite great attention in improving perinatal care, perinatal loss (fetal loss and newborn death) continues to occur. According to the World Health Organization (WHO), the perinatal period extends from the 20th gestational week through 1 month after birth. However, researchers who study perinatal loss use a broader definition that includes early (during the first 12 weeks following conception) as well as late fetal loss (>20 weeks’ gestation). Of all known pregnancies, an estimated ratio of 12% to 20% ends in an early fetal loss. The most recent available data have revealed that the rates translate to about 1.03 million annual fetal losses and, for 2004, 18.602 newborn deaths. According to the results of 2008, infant mortality rate decreased very rapidly in Turkey. Of the many parents who suffer a perinatal loss, at least 80% become pregnant again, an event that occurs within 18 months. Therefore, it is important for nurses and health care professionals to understand the impact of a perinatal loss on a subsequent pregnancy. The purpose of this article is to perform an investigation on parental, primarily maternal, responses to pregnancy subsequent to perinatal loss, and to describe nursing implications for parents during the subsequent pregnancy.